1997
DOI: 10.1103/physrevlett.78.705
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Conductance in Surface Superlattices by Temperature and Electric Field

Abstract: We present transport measurements on surface superlattices fabricated on a GaAs͞AlGaAs twodimensional electron gas. Significant suppression of the conductance is found with increasing electric fields and with increasing temperature T. We attribute these effects to e-e scattering, which can significantly affect the resistance in the presence of a spatially modulated static potential.[S0031-9007(96)02082-0] PACS numbers: 73.20.Dx, 73.50.Fq The concept of a lateral surface superlattice (SSL) dates back almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…[5][6][7] It has been found that the Van Hove singularity of the density of state inherent with the one dimensionality causes a characteristic electronic transport. 8,9 In this paper, we consider the charge transfer between an adatom localized state and a one-dimensional miniband associated with a quantum wire or quantum-dot array. The charge transfer between an adatom and a substrate semiconductor has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] It has been found that the Van Hove singularity of the density of state inherent with the one dimensionality causes a characteristic electronic transport. 8,9 In this paper, we consider the charge transfer between an adatom localized state and a one-dimensional miniband associated with a quantum wire or quantum-dot array. The charge transfer between an adatom and a substrate semiconductor has been extensively studied.…”
Section: Introductionmentioning
confidence: 99%
“…However, comparatively less attention has been given to the nonlinear ballistic transport regime in which electric fields or currents become so large that they significantly affect the momentum distribution of the carriers without destroying ballistic motion by inelastic scattering processes. Only recently has it been recognized in both theoretical and experimental studies that it is rather challenging to also investigate the nonlinear ballistic transport regime [6][7][8]. Even though several groups have realized that the introduction of artificial asymmetries should have a significant effect on nonlinear ballistic transport [9][10][11], so far, no strong nonlinear effects induced by a broken device symmetry have been observed.…”
mentioning
confidence: 99%
“…At T = 4.2 K, we find that the ballistic rectifier works when the input voltage is as low as 0.5 mV, the same order of k B T . Based on an extended Landauer-Büttiker formula for nonlinear transport, we show that even when the input signal is much smaller than k B T , temperature has no obvious influence on the rectification effect.c 1999 Academic Press Key words: nonlinearity, ballistic transport, rectification, threshold.There is increasing attention paid to nonlinear ballistic transport both experimentally [1][2][3][4][5] and theoretically [6][7][8][9][10][11]. Nonlinearity is important in mesoscopic conductors because of the small device feature sizes and the fact that in principle nonlinearity starts at any nonzero current.…”
mentioning
confidence: 99%